Efektifitas Kinerja Produksi Air Bersih pada Perusahaan Daerah Air Minum (PDAM) XYZ Menggunakan Metode Objective Matrix (OMAX) - Marlinda, Marlinda; Hartati, Rita; Hidjrawan, Yusi (Jurnal Optimalisasi, 2025)
This study aims to determine the performance of clean water production at PDAM XYZ. The method used is the Objective Matrix (OMAX). In the formation of the Omax matrix, values are required in the form of actual values, actual scores, productivity values, and descriptions of each ratio. The results of the study show that the Overall Productivity (OP) value shows that the productivity of the XYZ Regional Drinking Water Company (PDAM) in producing clean water as a whole from 2021 to 2024 has increased and decreased. The highest Overall Productivity (OP) value is in 2022 at 601, where overall the actual score for each ratio is not included in the bad category. The lowest Overall Productivity (OP) value is in 2023, this is because in 2023 for ratio 6, namely about effectiveness, which has an actual score of only 1, it is included in the bad category. After experiencing a decline in productivity, in 2024 the company's overall productivity value increased again. So it can be concluded that the best performance and productivity that occurred during 2021 to 2024 was in 2022, this can be seen from the overall productivity value in 2022 which was 601. Meanwhile, the worst performance and productivity occurred in 2023, this can be seen from the very low overall productivity value in 2023, which was only 388.